Synthesis and luminescent properties of CaF₂:Eu²⁺ nanocrystals - Zhmurin, P.N.; Sythik, O.Yu.; Svidlo, O.V.; Lebedev, V.N.; Adadurov, A.F. (Functional Materials, 2012)
The synthesis of CaF₂ nanocryatals activated by Eu²⁺ ions and soluble in nonpolar media is described, their luminescent properties are studied. It is shown that in nanocrystals of this type there are some channels of radiationless energy loss. These losses significantly decrease the quantum yield of luminescence of CaF₂ nanocryatals.